2020
DOI: 10.1039/d0na00591f
|View full text |Cite
|
Sign up to set email alerts
|

NiFe2O4nanoparticles: an efficient and reusable catalyst for the selective oxidation of benzyl alcohol to benzaldehyde under mild conditions

Abstract: Benzaldehyde is one of the most important and versatile organic chemicals for industrial applications. This study explores a milder approach for the fabrication of NiFe2O4 nanoparticles (NPs) for use as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 50 publications
(56 reference statements)
2
39
0
Order By: Relevance
“…The recent reported models for such type of oxidation use expensive metals 46 and their complexes, which are not easy to synthesize on an industrial scale such as the combination of two noble metals Au–Pd alloy along with ZrO 2 as the promoter, 47 few of which are accompanied by high temperature conditions. 3 Not many reports are available for this conversion catalyzed by Cu NPs and no report, particularly for CuS NPs, has been reported to the best of our knowledge. To test our photocatalyst for efficient selective conversion, benzyl alcohol was chosen as the model substrate and two reactions were carried out employing CS2 and CS20 as the photocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The recent reported models for such type of oxidation use expensive metals 46 and their complexes, which are not easy to synthesize on an industrial scale such as the combination of two noble metals Au–Pd alloy along with ZrO 2 as the promoter, 47 few of which are accompanied by high temperature conditions. 3 Not many reports are available for this conversion catalyzed by Cu NPs and no report, particularly for CuS NPs, has been reported to the best of our knowledge. To test our photocatalyst for efficient selective conversion, benzyl alcohol was chosen as the model substrate and two reactions were carried out employing CS2 and CS20 as the photocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C NMR spectra of benzyl alcohol and benzaldehyde are shown in Figure S10. As shown in Figure b, CeO 2 @N–C USHR exhibited production yield reaching above 99.9% after 48 h, which was the highest catalytic activity. , The catalytic activity of four samples followed the trend CeO 2 @N–C USHR > CeO 2 @C USHR > CeO 2 USHR > commercial CeO 2 . The above catalytic experiments indicated that both the morphology (hierarchical architecture assembled by ultrathin nanosheets) and the composite (N-doped C layer) have important effects on their catalytic activity.…”
Section: Resultsmentioning
confidence: 88%
“…These improvements have been made in order to increase the accessible sites/zones on the surface of catalyst, greater catalyst reactivity and selectivity, thermal stability and nally easy separation. Fe 3 O 4 , 12,13 NiFe 2 O 4 , [14][15][16] CoFe 2 O 4 , 17 CuFe 2 O 4 , [18][19][20] MnFe 2 O 4 , 21 Ni-Cu-ZnFe 2 O 4 , 22 BiFeO 3 , 23 FeAl 2 O 4 24 and ZnCrFeO 4 25 as a core, and metals, [26][27][28] silica, [29][30][31][32] polymers, [33][34][35] carbon nanotubes and sheets, [36][37][38][39][40] cellulose, 41 small organic molecules, 42,43 ionic liquids, 44,45 and organosulfonic acids 46,47 have been used as a coating.…”
Section: Introductionmentioning
confidence: 99%